Pelatihan Peningkatan Kompetensi AI Guru SD Melalui Pendekatan TPACK-AI - Dian Putri; Maya Dewi Kurnia; Taryo; Muhamad Riyad Ariwibowo; Rindi Wulandari (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service program aimed to enhance elementary school teachers' competence in integrating Artificial Intelligence (AI) into their pedagogical practices through the TPACK-AI framework. Conducted at SD Mitra in Cirebon City from August to September 2025, the program involved 10 certified teachers (7 female, 3 male) through a 5-week structured intervention consisting of preparation, intensive training, guided implementation, and evaluation phases. Using a quasi-experimental pre-post test design, data were collected through validated competency assessments, classroom observations, digital portfolios, and focus group discussions. Results showed significant improvements across four competency dimensions: conceptual understanding (from M=62.4 to M=86.7), technical skills in operating AI platforms (from M=58.3 to M=88.2), digital content creation abilities (from M=54.6 to M=84.5), and pedagogical integration capacity (from M=51.2 to M=82.8). Participant satisfaction averaged 4.52/5.0, indicating high program effectiveness. However, challenges persisted including unstable internet access (30%), time constraints (40%), and limited institutional support (20%). The program demonstrated that structured, hands-on training combined with guided implementation effectively transforms teaching practices, contributing to national digital literacy efforts in education